The Contributing Factors of Carbon Footprints Among Hotels on the Island of Mauritius: A Comparative Analysis - Toshima, Makoondlall-Chadee; Naadir, Goolamally; Ramasamy-Coolen, Priya; Chandradeo, Bokhoree; Ravi, Foogoa (European Journal of Sustainable Development, 2021)
The tourism and hospitality industry is a worldwide known trillion-dollar industry and a major economic generator for several economies. Despite a positive economic contributor, the challenges of the tourism industry cannot be overlooked. The tourism industry is right now definitely more involved on the broader aspects of sustainable tourism but nevertheless still contributes 8% of the GHG emissions globally. This work aims at identifying and addressing the main contributing areas responsible for the greenhouse gas emissions for the hotel industry in Mauritius. A quantitative approach based on an adapted framework of the hotel carbon measurement initiative (HCMI) was used to collect data from four hotels with different ratings and which were selected through convenience sampling. Land use for buildings, energy consumption and emissions, refrigerants being used in the hotel, water consumption and wastes being produced are researched as major contributors of GHG from the hotels and these were captured and analyzed. Comparatively, the findings revealed that the carbon footprint for 4-star, 5-star and 5-star plus hotels were found to be lower than the average carbon footprint of other hotels of similar categories worldwide. However, for 3-star hotels, the latter was found to be higher. Plausible recommendations were made accordingly to reduce carbon emissions for each hotel type.